2015
DOI: 10.1038/srep08476
|View full text |Cite
|
Sign up to set email alerts
|

Illumina sequencing-based analysis of free-living bacterial community dynamics during an Akashiwo sanguine bloom in Xiamen sea, China

Abstract: Although phytoplankton are the major source of marine dissolved organic matter (DOM), their blooms are a global problem that can greatly affect marine ecological systems, especially free-living bacteria, which are the primary DOM degraders. In this study, we analyzed free-living bacterial communities from Xiamen sea during an Akashiwo sanguine bloom using Illumina MiSeq sequencing of 16S rRNA gene amplicons. The bloom was probably stimulated by low salinity and ended after abatement of eutrophication pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 85 publications
14
64
0
Order By: Relevance
“…The bacterial OTUs and Shannon diversity obtained in the present study are more than two orders of magnitude and twofold higher than the results acquired via low‐profiling biology techniques for the same/similar eutrophication lakes (Zhao et al., ; Szabó et al., ), which is similar to that found by the high‐throughput pyrosequencing method (Zhang et al., ), suggesting that high‐throughput sequencing techniques are needed to decipher the overall bacterial diversity of lacustrine ecosystems. The relatively simple and stable bacterial community structure in the eutrophication region (A‐1 and A‐2) in comparison to the complexity in the mesotrophic water (A‐3) revealed by this study is consistent with the observations made in Xiamen Sea (Yang et al., ), indicating the effect of trophic status on the bacterial diversity may be similar in both marine and freshwater environments.…”
Section: Discussionsupporting
confidence: 91%
“…The bacterial OTUs and Shannon diversity obtained in the present study are more than two orders of magnitude and twofold higher than the results acquired via low‐profiling biology techniques for the same/similar eutrophication lakes (Zhao et al., ; Szabó et al., ), which is similar to that found by the high‐throughput pyrosequencing method (Zhang et al., ), suggesting that high‐throughput sequencing techniques are needed to decipher the overall bacterial diversity of lacustrine ecosystems. The relatively simple and stable bacterial community structure in the eutrophication region (A‐1 and A‐2) in comparison to the complexity in the mesotrophic water (A‐3) revealed by this study is consistent with the observations made in Xiamen Sea (Yang et al., ), indicating the effect of trophic status on the bacterial diversity may be similar in both marine and freshwater environments.…”
Section: Discussionsupporting
confidence: 91%
“…Candidate divisions (TM7, OD1, WS3, BRC1, and OP11) and unclassified organisms were also found in this study using Illumina MiSeq. This direct molecular approach successfully detected previously uncultured organisms belonging to candidate divisions, as has been previously observed (Yang et al 2015). All of these candidate divisions have been detected in environmental samples such as sediments and bioaerosols of a coal mine (Basak et al 2014; Wei et al 2015).…”
Section: Discussionsupporting
confidence: 70%
“…A similar succession pattern was previously observed in the North Sea (Teeling et al 2016). Polaribacter is a recurrent genus in the Baltic Sea during phytoplankton blooms (Laas et al 2015, Bunse et al 2016, while the NS3a marine group (and Flavobacteriia in general) have been observed during dinoflagellate blooms (Fandino et al 2001, Yang et al 2015.…”
Section: Bacterial Bloom Phasesupporting
confidence: 53%